Case presentation: a novel way of treating acute cauliflower ear in a professional rugby player. Issue 6 (23rd May 2005) - Macdonald, D J M; Calder, N; Perrett, G; McGuiness, R G
Abstract : Acute auricular haematoma is a common problem in rugby players and can be difficult to treat due to re-accumulation of the fluid and can subsequently cause the unsightly cauliflower ear. We present a case of auricular haematoma affecting the central part of the pinna in a professional rugby player. This was treated successfully by aspiration and the use of silicone splints which allowed the player to continue training and competing.